Information management and big data : 4th Annual International Symposium, SIMBig 2017, Lima, Peru, September 4-6, 2017, Revised selected papers /: 4th Annual International Symposium, SIMBig 2017, Lima, Peru, September 4-6, 2017, Revised selected papers. (2018) - Unknown
No abstract available